GLP-1 Receptor Agonists for Hepatic Steatosis and Fibrosis in Type 2 Diabetes with NAFLD. - Mishal Rizwan, Alveena Fareed, Sarah Khan, Ali Hassan, FNU Nikeeta, Haleema Hammad, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Glucagon-like peptide-1 receptor agonists (GLP-1RAs) may attenuate hepatic steatosis andmodify fibrosis risk in type 2 diabetes mellitus (T2D) with nonalcoholic fatty liver disease. Thisprospective, parallel-group study evaluated once-weekly semaglutide added to standard diabetes care versus standard care alone over 48 weeks in adults with T2D